Law on e-transactions - The National Assembly (2005)
This Law provides for e-transactions in the operations of state agencies; the civil, business, commercial and other sectors prescribed by law. The provisions of this Law shall not apply to the grant of certificates of land use rights, house ownership right and immovable properties, inheritance documents, marriage certificates, divorce decisions, birth certificates, death certificates, bills of exchange and other valuable papers